Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Siswa di Lingkungan Sekolah Melalui Kegiatan Muhadhoroh di SMK Muhammadiyah 6 Modo - Haniza Nur Octavia; Mahbub Junaidi; Zuli Dwi Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in shaping students' character through muhadhoroh activities at SMK Muhammadiyah 6 Modo. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The results indicate that PAI teachers are involved in designing, guiding, and evaluating muhadhoroh as a medium for character building. The characters developed include responsibility, courage, discipline, self-confidence, and leadership. Challenges encountered include limited student interest, time constraints, and inadequate facilities. Efforts to overcome these challenges involve providing motivation, actively engaging students, and enhancing teacher collaboration. The study concludes that muhadhoroh activities play a strategic role in character development when supported by the consistent and structured involvement of PAI teachers.